Being a young midwifery student: A qualitative exploration. (August 2016) - Fenwick, J.; Cullen, D; Gamble, J.; Sidebotham, M.
Abstract: Background: undergraduate midwifery programmes offer opportunities for school leavers and young people (aged less than 21 years) to enter the profession. There is limited research exploring this age groups experience of their Bachelor of Midwifery programme. In order to retain these students we need to ensure that their experiences of undertaking a Bachelor of Midwifery program are positive and barriers and challenges are minimised. Aim: this study explored young midwifery students' experience of their Bachelor of Midwifery program. Method: a descriptive exploratory qualitative approach was used to explore the experiences of eleven students aged 20 years or less on enrolment. Data was collected using face-to-face or telephone-recorded interviews. Thematic analysis was used to analysis the data set. Findings: three major themes described the young students' experiences. The first labelled 'The challenges of being young' presented a number of age related challenges including transport issues with on-call commitments as some students had not gained a driver's license. Students experienced some degree of prejudice relating to their age from their older student peers and some clinical staff during placements. 'Finding your way' was the second theme and described the strategies students used to build confidence and competence both in the university and clinical environment. The young students reported a strong commitment to the profession. They demonstrated high levels of connection with women and found the continuity of care experiences invaluable to their learning. The final theme 'Making the transition from teenager to midwife' demonstrated some unique insights into how studying to become a midwife impacted upon their personal and professional growth. Conclusion: the young students in this study encountered some unique issues related to their age. However as they progressed through the program they developed confidence in themselves and visualised themselves as having a long midwifery career. They were strongly motivated towards providing woman-centred maternity care and considered their continuity of care experiences fundamental to them developing a strong sense of themselves as midwives. Attracting and retaining young students is essential if the profession is to realise its goal of ensuring all women have access to a known midwife. Highlights: Midwifery programmes may assist with maturation and transition to adult hood for young midwifery students. The continuity of care experience is fundamental to young midwife student's transition to midwifery. Young Midwifery students develop resilience and coping strategies over time. Young midwifery students demonstrate commitment to a career in midwifery. The attraction and retention of school leavers into midwifery should be integrated into workforce Planning.